A Comparative Evaluation of the Total Cost of Ownership between Electric Two-Wheelers and Motorized Two-Wheelers from an Indian Perspective. Issue 5 (May 2022) - Patil, Mallikarjun; Bandhu Majumdar, Bandhan; Kumar Sahu, Prasanta
A comparative assessment of the total cost of ownership (TCO) is necessary to quantify overall costs and assess the economic viability of electric two-wheelers (E2W) compared with motorized two-wheelers (M2W). In this regard, TCO models specifically for two-wheelers were developed in this study to compare the TCO of E2W and M2W under the prevailing market conditions. The TCO model has four cost components, namely, acquisition costs, operating costs, maintenance costs, and resale value. The TCO was calculated considering a 10-year assessment period with 2021 as the base year. The available E2W and M2W alternatives in the Indian market were classified into low-performance (Category A) and high-performance (Category B) two-wheelers based on their power output and acceleration characteristics. The TCO estimates were also evaluated for three different average daily distances traveled ( ADDT ): 10 km/day, 30 km/day, and 50 km/day. The results revealed that the TCO estimates for E2W vary from ₹0.67/km for an ADDT of 50 km/day for Category A E2W during the base year condition to₹7.66/km for an ADDT of 10 km/day for Category B E2W at the end of the assessment period. Further, the payback periods for different scenarios were also estimated and compared. The acquisition and battery replacement costs are critical factors for potential users of E2W, and act as a significant barrier to the widespread adoption of E2W in India. Finally, it can be concluded that E2W are an economically viable alternative compared with M2W, with payback periods ranging from one year to eight years in the Indian context.